2013
DOI: 10.1016/j.meegid.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of swine influenza H3N2 in the United States: Translational public health for zoonotic disease surveillance

Abstract: The field of phylogeography has received a lot of attention for its application to molecular evolution and geographic migration of species. More recent work has included infectious diseases especially zoonotic RNA viruses like influenza and rabies. Phylogeography of viruses has the potential to advance surveillance at agencies such as public health departments, agriculture departments, and wildlife agencies. However, little is known about how these agencies could use phylogeography for applied surveillance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The state of Minnesota was inferred to be the ancestral location of human-like H3 viruses isolated from outbreaks observed between 2009 and 2012 (118), which agrees with our TMRCAs inferred from HA segment (Figure 3). However, results of the SG + UCLN symmetric model, selected as the best fitting model for HA sequence data (Supplementary Table 4), implicates the state of Iowa as the ancestral region (after 2013) for currently circulating human-like H3 viruses, followed by the state of Minnesota as a secondary ancestral location (Figure 5H).…”
Section: Updated Insights In the Evolutionary Epidemiology Of Swine Isupporting
confidence: 86%
See 2 more Smart Citations
“…The state of Minnesota was inferred to be the ancestral location of human-like H3 viruses isolated from outbreaks observed between 2009 and 2012 (118), which agrees with our TMRCAs inferred from HA segment (Figure 3). However, results of the SG + UCLN symmetric model, selected as the best fitting model for HA sequence data (Supplementary Table 4), implicates the state of Iowa as the ancestral region (after 2013) for currently circulating human-like H3 viruses, followed by the state of Minnesota as a secondary ancestral location (Figure 5H).…”
Section: Updated Insights In the Evolutionary Epidemiology Of Swine Isupporting
confidence: 86%
“…Yet, we were able to infer this particular route as significant using both the HA and the PB2 segments (Figures 7H, 8D). Additionally, Scotch et al (118) confirmed agreements in the phylogeographic inferences between HA and NA gene segments. This highlights another decisive question about the suitability and efficiency of using single, multiple, or whole genome when using phylodynamic methods for molecular surveillance of viral diseases.…”
Section: Robustness and Limitations Of Phylodynamic Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the integration of phylodynamic methods as a standard tool for molecular surveillance of PRRSv might support the development of effective (and efficient) policy decisions for the control and prevention of this virus in identified high-risk epidemiological settings. However, continued efforts will be needed to build on current achievements, in order to expand and update databases containing information on swine population and practices, and PRRSv incidence and genomic data, and to build efficient bioinformatics and computational infrastructures, basic requirements for the field of applied phylodynamics [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a homeopathic approach against H3N2 was investigated by Siqueira et al,28 demonstrating positive results. In an effort for early detection of H3N2, Scotch and Mei29 proposed a system of phylogeography in the United States. There are very few studies simultaneously presenting clinical and laboratory findings from H3N2 and H1N1 patients within the same influenza wave of 2013, therefore we consider that our data will provide useful information for current and future investigational studies with a novel statistical methodology 1216…”
Section: Introductionmentioning
confidence: 99%